2005
DOI: 10.1038/oby.2005.162
|View full text |Cite
|
Sign up to set email alerts
|

Body Composition and Hormonal Adaptations Associated with Forskolin Consumption in Overweight and Obese Men

Abstract: GODARD, MICHAEL P., BRAD A. JOHNSON, AND SCOTT R. RICHMOND. Body composition and hormonal adaptations associated with forskolin consumption in overweight and obese men. Obes Res. 2005;13:1335-1343. Objective: This study examined the effect of forskolin on body composition, testosterone, metabolic rate, and blood pressure in overweight and obese (BMI Ն 26 kg/m 2 ) men. Research Methods and Procedure: Thirty subjects (forskolin, n ϭ 15; placebo, n ϭ 15) were studied in a randomized, double-blind, placebo-control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
83
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(91 citation statements)
references
References 28 publications
6
83
1
1
Order By: Relevance
“…It has been previously reported that FSK dramatically increased SF-1 protein and mRNA levels by repressing DAX-1 protein and mRNA expression [39]. The clinical study also observed the role of FSK in significantly increasing lean muscle mass, bone mass, and testosterone in overweight and obese men [40].…”
Section: Discussionsupporting
confidence: 49%
“…It has been previously reported that FSK dramatically increased SF-1 protein and mRNA levels by repressing DAX-1 protein and mRNA expression [39]. The clinical study also observed the role of FSK in significantly increasing lean muscle mass, bone mass, and testosterone in overweight and obese men [40].…”
Section: Discussionsupporting
confidence: 49%
“…Lastly, Coleus forskohlii extracts with varying and undefined FSK content are widely and uncritically used as dietary supplement for weight reduction (Rios-Hoyo and GutierrezSalmean, 2016). The available clinical evidence (Godard et al, 2005) is insufficient to recommend the use of FSK for treatment of obesity.…”
Section: Clinical Applications Of Diterpenesmentioning
confidence: 99%
“…This plant, which comes from the mountains of Asia, has been used for centuries in tradition of India cuisine (pickles) and more recently in formulation of Ayurveda medicines (Badmaev, Majeed, Conte, & Parker, 2002;Godard, Johnson, & Richmond, 2005). Coleus forskohlii supports fat loss through a cascade of chemical reactions -especially its ability to facilitate the action of hormones via hormonal second messenger cyclic AMP and also preventing triacylglycerol lipase mechanism.…”
Section: Introductionmentioning
confidence: 99%